Influence of biodegradation on the organic compounds composition of peat - Serebrennikova O. V. Olga Viktorovna; Svarovskay L. I. Lidiya Ivanovna; Duchko M. A. Mariya Aleksandrovna; Strelnikova E. B.; Russkikh I. V. (2016, 2016)
Title screen